2014
DOI: 10.1002/macp.201400072
|View full text |Cite
|
Sign up to set email alerts
|

Absorption and Scattering in Concentrated Monomer Miniemulsions: Static and Dynamic Investigations

Abstract: Low-scattering monomer miniemulsions have recently emerged as a suitable system for the development of effi cient photopolymerization processes in dispersed media. Since their reactivity under UV exposure is strongly dependent on their optical properties, there is a strong interest to fi nd simple analytical methods for studying absorption and scattering with readyto-polymerize concentrated miniemulsions, while avoiding dilution. This paper focuses on three types of concentrated miniemulsions without photoinit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 41 publications
0
25
0
Order By: Relevance
“…[ 22 ] Scattering and absorption coeffi cients of acrylate miniemulsions were also determined in diluted [ 22 ] and concentrated [ 23 ] media using an integration sphere or the Kubelka-Munk theory, respectively. In this work, we employed a simple spectroscopic set-up to assess light penetration.…”
Section: Resultsmentioning
confidence: 99%
“…[ 22 ] Scattering and absorption coeffi cients of acrylate miniemulsions were also determined in diluted [ 22 ] and concentrated [ 23 ] media using an integration sphere or the Kubelka-Munk theory, respectively. In this work, we employed a simple spectroscopic set-up to assess light penetration.…”
Section: Resultsmentioning
confidence: 99%
“…According to the Beer–Lambert law, the absorbance ( A ) at wavelength λ can be expressed by Aλ=Eλ . l where E is the attenuation coefficient, l the optical path length. The attenuation coefficient can be separated into three components; the absorption coefficient from C4AzoTAB ( K C 4 AzoTAB ), the absorption coefficient from PSt particles (swollen with monomer in case of incomplete conversion) ( K PSt ) and the scattering coefficient from PSt particles ( S PSt ): E =KC4AzoTAB +KPSt+SPSt…”
Section: Methodsmentioning
confidence: 99%
“…Previous work reported that the main factor responsible for the high attenuation of waterborne dispersion was scattering rather than absorption . It can thus be presumed that the colloidal stability despite the UV irradiation is caused by the high scattering ( S λ ) of UV light at 365 nm by PSt particles, thus reducing the efficiency of the C4AzoTAB trans to cis photoisomerization even under vigorous stirring conditions…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Photo‐initiated polymerization of monomer droplets or particles dispersed in a liquid medium is an appealing approach to prepare dispersions of polymers by avoiding any source of heat. The principle has been documented for over two decades where, for instance, the radical polymerization of (meth)acrylates in conventional emulsion polymerization, in microemulsion and more recently in miniemulsion has been described in several papers and patents . Lately, miniemulsion photopolymerization has enjoyed particular attention due to its versatility for the preparation of polymer particles with virtually endless options in terms of composition and structure .…”
Section: Introductionmentioning
confidence: 99%